Peran Komunikasi Empatik Bidan Dalam Menurunkan Kecemasan Ibu Primigravida Saat Bersalin - Indra Fara Nisa; Aditia Silvia Fazila; Laode Aharuddin Kapege (CV. ITTC INDONESIA, 2025)
High levels of anxiety in primigravida mothers during childbirth can adversely affect the labor process, both physiologically and psychologically. Empathetic communication by midwives, as primary care providers, plays a crucial role in establishing a therapeutic relationship that supports the mother’s emotional well-being. This study aims to analyze the role of midwives' empathetic communication in reducing anxiety levels among primigravida mothers during labor. A quantitative research approach was employed using a quasi-experimental pretest-posttest design with a control group. The results showed a significant reduction in anxiety levels in the group that received empathetic communication compared to the control group. These findings confirm that empathetic communication is an effective strategy for managing anxiety in primigravida mothers.